Glacial oscillations during the Bølling–Allerød Interstadial–Younger Dryas transition in the Ruda Valley, Central Pyrenees - Fernandes, Marcelo (2022)
The Upper Garonne Basin included the largest glacial system in the Pyrenees during the last glacialcycle. Within the long‐term glacial retreat during Termination‐1(T‐1), glacier fluctuations left geomorphic evidencein the area. However, the chronology of T‐1 glacial oscillations on the northern slopes of the Central Pyrenees is stillpoorly constrained. Here, we introduce new geomorphological observations and a 12‐sample dataset of10Becosmic‐ray exposure ages from the Ruda Valley. This U‐shaped valley, surrounded by peaks exceeding 2800 m a.s.l.,includes a sequence of moraines and polished surfaces that enabled a reconstruction of the chronology of the lastdeglaciation. Following the maximum ice extent, warmer conditions prevailing at ~15–14 ka, during theBølling–Allerød (B–A) Interstadial, favoured glacial retreat in the Ruda Valley. Within the B–A, glaciers experiencedtwo phases of advance/stillstand with moraine formation at 13.5 and 13.0 ka. During the early Younger Dryas (YD),glacial retreat exposed the highest surfaces of the Saboredo Cirque (~2300–2350 m) at 12.7 ka. Small glacierspersisted only inside the highest cirques (~2470 m), such as in Sendrosa Cirque, with moraines stabilising at 12.6 ka.The results of this work present the most complete chronology for Pyrenean glacial oscillations from the B–A to theYD